2015
DOI: 10.1177/1934578x1501000913
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial Activity of Isoquinoline Alkaloids from the Stem Bark of Actinodaphne macrophylla

Abstract: Seven isoquinoline alkaloids isolated from the bark of Actinodaphne macrophylla in this study demonstrated in vitro antiplasmodial activities against Plasmodium falciparum 3D7 with IC 50 values of 0.08 μM, 0.05 μM, 1.18 μM, 3.11 μM, 0.65 μM, 0.26 μM, and 1.38 μM for cycleanine, 10demethylxylopinine, reticuline, laurotetanine, bicuculine, -hydrastine and anolobine, respectively, which are comparable with the reference standard, chloroquine. 10-Demethylxylopinine was found to be the most active of these compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Since the most strong synthetic or natural product driven AChE inhibitors are known to contain nitrogen, the promising activity of both Actinodaphne extracts could be due to their high alkaloidal contents (29)(30). These results were in accordance with the previous phytochemical studies of both species, which found to have alkaloids as their major compounds (14)(15).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Since the most strong synthetic or natural product driven AChE inhibitors are known to contain nitrogen, the promising activity of both Actinodaphne extracts could be due to their high alkaloidal contents (29)(30). These results were in accordance with the previous phytochemical studies of both species, which found to have alkaloids as their major compounds (14)(15).…”
Section: Resultssupporting
confidence: 89%
“…From the literature survey, Actinodaphne species have been reported to have antimicrobial (9), hepatoprotective (10), anti-inflammatory (11), antibacterial (12) and antioxidant (13) activities. Phytochemistry of A. macrophylla has been studied and resulted in the isolation of isoquinoline alkaloids and their antimalarial activities (14). In addition, phytochemical study on A. pruinosa were successfully isolated aporphines alkaloids and their cytotoxicity activity (15).…”
Section: Introductionmentioning
confidence: 99%
“…2-Norcepharanthine (29) and cycleanine have strong antiplasmodial activities against P. falciparum D6 at similar IC 50 about 80 nM compared with chloroquine (IC 50 6.18 ± 0.71 nM) (Angerhofer et al 1999). The result of cycleanine in this study was consistent with that of Fadaeinasab's study (Fadaeinasab et al 2015). Yet the cytotoxicity of 2-norcepharanthine and cycleanine need to be assessed.…”
Section: Antimicrobial Effectssupporting
confidence: 88%
“…Northalrugosidine (28) showed the most potent in vitro activity against Leishmania donovani promastigotes (0.28 lM), and the highest selectivity (29.3-fold) versus its general cytotoxicity against HT-29 human colon adenocarcinoma cells (Naman et al 2015). Meanwhile the reduction in parasite burden to the murine spleen and liver after the in vivo testing of northalrugosidine at 2.8, 5.6, and 11.1 mg/kg per animal when administered intravenously supported the idea that it could be further investigated as a potential new drug candidate or lead molecule for drug discovery (Naman et al ,9, 10, 21, 25, 28, 29, 52 Ye and Dyke (1989), Ye et al ( , 2013, Chen et al (2002Chen et al ( , 2003, Chea et al (2010), Baghdikian et al (2013), Fadaeinasab et al (2015), Naman et al (2015) Antibacterial effects 9, 52 Lee et al (2011Lee et al ( , 2012, Avci et al (2018), Yin et al (2015) Antifungal effects 9, 49, 52 Li and Zhang (2006) Anti-inflammatory effects 1, 5, 9, 10, 21, 25, 39, 49 Guo et al (20151, 5, 9, 10, 21, 25, 39, 49 Guo et al ( , 2018 1,9,10,21,25,39,50,52 Bhagya and Chandrashekar (2018) Wong et al (2000), Rao (2002), Huang et al (1999), Li et al (2001Li et al ( , 2003, Zhou et al (2007), Pinelli et al (2010), Shen et al (1999), Young et al (1994), Orallo (2004), Yu et al (1993),…”
Section: Antimicrobial Effectsmentioning
confidence: 93%
See 1 more Smart Citation